Development of a Cherenkov-type diagnostic system to study runaway electrons within the COMPASS tokamak. (26th October 2017) - Rabinski, M.; Jakubowski, L.; Malinowski, K.; Sadowski, M.J.; Zebrowski, J.; Jakubowski, M.J.; Mirowski, R.; Weinzettl, V.; Ficker, O.; Mlynar, J.; Panek, R.; Paprok, R.; et al.
Abstract: Direct measurements of fast electrons, which are produced in high-temperature plasma and escape from tokamak-type facilities, are of particular interest for ITER and future fusion devices, where intense runaway electrons (RE) can significantly damage the first wall components. Therefore, the runaway control and mitigation based on credible measuring methods should be developed already in present devices. A team from the National Centre for Nuclear Research (NCBJ), Poland, developed special probes equipped with Cherenkov-type detectors for measurements of the fast electrons within edge plasmas of tokamaks. Studies of the fast runaway electrons were extensively carried out at the COMPASS tokamak at the Institute of Plasma Physics (IPP) in Prague during experimental campaigns in 2014–2016. In order to investigate an electron-beam energy distribution a three-channel probe equipped with the Cherenkov-type detectors sensitive to electrons of different energies has been constructed. The measurements performed by means of these detectors showed that the first fast electron peak appears usually in the current ramp-up phase, even before the hard X-rays (HXR) pulse. Some electron signals can also be observed during subsequent HXR emissions. However, the most distinct electron peaks in all energy channels appear mainly during the plasma disruption. A correlation of Cherenkov signals with the MHD activity was also studied.